Miniature gold nanorods for photoacoustic molecular imaging in the second near-infrared optical window - Chen, Yun-Sheng; Zhao, Yang; Yoon, Soon Joon; Gambhir, Sanjiv Sam; Emelianov, Stanislav (Nature nanotechnology, 2019)
In photoacoustic imaging, the second near-infrared (NIR-II) window is where tissue generates the least background signal. However, the large size of the few available contrast agents in this spectral range impedes their pharmacokinetics and decreases their thermal stability, leading to unreliable photoacoustic imaging. Here, we report the synthesis of miniaturized gold nanorods absorbing in the NIR-II that are 5-11 times smaller than regular-sized gold nanorods with a similar aspect ratio. Under nanosecond pulsed laser illumination, small nanorods are about 3 times more thermally stable and generate 3.5 times stronger photoacoustic signal than their absorption-matched larger counterparts. These unexpected findings are confirmed using theoretical and numerical analysis, showing that photoacoustic signal is not only proportional to the optical absorption of the nanoparticle solution but also to the surface-to-volume ratio of the nanoparticles. In living tumour-bearing mice, these small targeted nanorods display a 30% improvement in efficiency of agent delivery to tumours and generate 4.5 times greater photoacoustic contrast.